Simulating southwestern U.S. desert dust influences on severe, tornadic storms - Lerach, David Gregory, author; Cotton, William R., advisor; Rutledge, Steven A., committee member; Kreidenweis, Sonia M., committee member; Roesner, Larry A., committee member (Colorado State University. Libraries, 2012)
In this study, three-dimensional numerical simulations were performed using the Regional Atmospheric Modeling System (RAMS) model to investigate possible southwestern U.S. desert dust impacts on severe, tornadic storms. Initially, two sets of simulations were conducted for an idealized supercell thunderstorm. In the first set, two numerical simulations were performed to assess the impacts of increased aerosol concentrations acting as cloud condensation nuclei (CCN) and giant CCN (GCCN). Initial profiles of CCN and GCCN concentrations were set to represent "clean" continental and aerosol-polluted environments, respectively. With a reduction in warm- and cold-rain processes, the polluted environment produced a longer-lived supercell with a well-defined rear flank downdraft (RFD) and relatively weak forward flank downdraft (FFD) that produced weak evaporative cooling, a weak cold-pool, and an EF-1 tornado. The clean environment produced no tornado and was less favorable for tornadogenesis. In the second ensemble, aerosol microphysical effects were put into context with those of convective available potential energy (CAPE) and low-level moisture. Simulations initialized with greater low-level moisture and higher CAPE produced significantly stronger precipitation, which resulted in greater evaporation and associated cooling, thus producing stronger cold-pools at the surface associated with both the forward- and rear-flank downdrafts. Simulations initialized with higher CCN concentrations resulted in reduced warm rain and more supercooled water aloft, creating larger anvils with less ice mass available for precipitation. These simulated supercells underwent less evaporative cooling within downdrafts and produced weaker cold-pools compared to the lower CCN simulations. Tornadogenesis was related to the size, strength, and location of the FFD- and RFD-based cold-pools. The combined influence of low-level moisture and CAPE played a considerably larger role on tornadogenesis compared to aerosol impacts. However, the aerosol effect was still evident. In both idealized model ensembles, the strongest, longest-lived tornado-like vortices were associated with warmer and weaker cold-pools, higher CAPE, and less negative buoyancy in the near-vortex environment compared to those storms that produced shorter-lived, weaker vortices. A final set of nested grid simulations were performed to evaluate dust indirect microphysical and direct radiative impacts on a severe storms outbreak that occurred during 15-16 April 2003 in Texas and Oklahoma. In one simulation, neither dust microphysical nor radiative effects were included (CTL). In a second simulation, only dust radiative effects were considered (RAD). In a third simulation, both dust radiative and indirect microphysical effects were simulated (DST), where dust was allowed to serve as CCN, GCCN, and ice nuclei (IN). Fine mode dust serving as CCN reduced warm rain formation in the DST simulation. Thus, cloud droplets were transported into the mixed phase region, enhancing freezing, aggregation, and graupel and hail production. However, graupel and hail were of smaller sizes in the DST simulation due to reduced riming efficiencies. Dust particles serving as GCCN and IN played secondary roles, as these impacts were offset by other processes. The DST simulation yielded the lowest rainfall rates and accumulated precipitation, as much of the total water mass within the convective cells were in the form of aggregates and small graupel particles that were transported into the anvil region rather than falling as precipitation. The combined effects of warm rain efficiency, ice production, and hydrometeor size controlled the evolution of cold-pools and storm structure. The RAD and CTL simulations produced widespread cold-pools, which hindered the formation of long-lived supercells relative to the DST simulation. The DST convective line was associated with reduced rainfall and multiple long-lived supercells. Comparisons between the RAD and CTL simulations revealed that dust radiative influences played an important role in convective initiation. The increased absorption of solar radiation within the dust plume in the RAD simulation warmed the dust layer over time, which reduced the amount of radiation that reached the surface, resulting in slight cooling at the surface and increased atmospheric stability within the lowest 2 km. Dew points at low levels were slightly lower in the RAD simulation, due to reduced surface water vapor fluxes (latent heat fluxes) below the dust plume. With the presence of a stronger capping inversion but more available low-level moisture, the CTL simulation initially produced more widespread convection and precipitation, while the RAD simulation produced the strongest convective cores, including a long-lived supercell. The results from all three sets of simulations suggest that dust indirect microphysical and direct radiative impacts on severe convection may at times greatly influence the development of severe storms. In this study, dust often increased the potential for tornadogenesis. Additional modeling studies at horizontal grid spacing ≤100 m are needed in order to address the robustness of these results and better isolate potential dust influences on severe storms and tornadogenesis.
Keywords: aerosol; tornadoes; supercells; dust